Continuous casting crystallizer casting powder for medium-carbon high-chromium steel billets as well as preparation method and application of continuous casting crystallizer casting powder
By designing a continuous casting crystallizer with suitable chemical composition to protect the slag, using raw materials such as modified fly ash and discarded shells in the seafood processing industry, the problem of poor lubrication effect of medium-carbon high-chromium steel billets during continuous casting is solved, and the effect of reducing cracks, improving heat flow effect and improving yield is achieved.
Patent Information
- Application Number
- CN202510013017.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-28
AI Technical Summary
During the continuous casting process, medium-carbon high-chromium steel billets have high shell strength and high brittleness, and the lubricity of the protective slag does not meet the requirements, resulting in cracks and other defects on the surface of the product, reducing the yield rate.
A continuous casting crystallizer protective slag for medium-carbon high chromium billets was designed, with chemical compositions of CaO 25.6~26.5%, SiO2 40~45%, Al2O3 6~11%, Na2CO3 8~10.3%, ZnO 5.4~8.5% and balance of modified fly ash. Fly ash was modified by sodium polyphosphate and DL-tartaric acid to form a protective slag with good lubrication effect.
The protective slag has a good lubrication effect, reduces crack generation, is suitable for melting point and viscosity, improves the heat flow effect in the crystallizer, reduces the quality problem of medium-carbon and high-chromium steel billets, and improves the yield rate. At the same time, the use of discarded shells in the seafood processing industry and fly ash in the power plant has reduced environmental pollution and improved the comprehensive utilization rate of resources.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of continuous casting mold protection slag, and in particular to continuous casting mold protection slag for medium carbon high chromium steel billets, and a preparation method and application thereof. Background Art
[0002] The continuous casting mold protection slag plays a vital role in the continuous casting process. It is located between the molten steel and the copper wall in the mold, and mainly plays the role of lubrication, heat preservation, preventing the oxidation of the molten steel and absorbing inclusions.
[0003] However, in actual production, due to the relatively high shell strength and brittleness of medium-carbon high-chromium steel billets, the lubrication effect of the protective slag still does not meet the requirements, and there is still a risk of defects such as surface cracks on the product, which reduces the yield.
[0004] Based on this, the present invention designs continuous casting mold protection slag for medium carbon high chromium steel billet and its preparation method and application to solve the above problems. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides continuous casting mold protection slag for medium-carbon high-chromium steel billets and a preparation method and application thereof.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: The invention discloses a continuous casting mold protection slag for medium carbon high chromium steel billet, wherein the chemical composition and weight percentage thereof are as follows: CaO 25.6-26.5%, SiO2 40-45%, Al2O3 6-11%, Na2CO3 8-10.3%, ZnO 5.4-8.5% and the balance is modified fly ash; the modified fly ash is the product of fly ash modified by sodium polyphosphate and DL-tartaric acid.
[0007] Furthermore, the mass ratio of the sodium polyphosphate to DL-tartaric acid is 1:0.3-0.6.
[0008] Furthermore, the mass ratio of the sodium polyphosphate to fly ash is 3.2-6.5:100.
[0009] Furthermore, the preparation method of the modified fly ash is: (1) Ultrafinely grinding fly ash to a particle size of 5-10 μm to obtain ultrafine fly ash powder; (2) Dissolve DL-tartaric acid in water to prepare a 1-3% DL-tartaric acid solution; stir the ultrafine fly ash powder at a low speed of 50-100 rmin, and spray the DL-tartaric acid solution on the ultrafine fly ash powder using a spraying device, and control the temperature below 35°C; after spraying, the DL-tartaric acid solution covers the surface of the ultrafine fly ash powder, and then quickly heats to 150-155°C and stirs for reaction for 3-5 hours; The concentration of DL-tartaric acid solution increases rapidly. Due to the fast heating speed, the DL-tartaric acid solution on the surface of the fly ash ultrafine powder boils locally, forming small bubbles, leaving some tiny pits or traces on the surface of the fly ash ultrafine powder. When the water is completely evaporated, DL-tartaric acid will form a solid film on the surface of the fly ash ultrafine powder. (3) Dissolve sodium polyphosphate in hot water at 90-92°C to prepare a 4-5% sodium polyphosphate solution, spray the sodium polyphosphate solution on the ultrafine fly ash powder using a spraying device, stir and react for 1-2 hours at a reaction temperature of 155-182°C to obtain modified fly ash.
[0010] Furthermore, the CaO is derived from shell calcination products discarded from the seafood processing industry.
[0011] Furthermore, SiO2 is derived from river sand, and the SiO2 content is above 80%.
[0012] Furthermore, Al2O3 is derived from diaspore, and the Al2O3 content is above 85%.
[0013] Furthermore, the fly ash comes from power plant fly ash.
[0014] In order to better achieve the purpose of the present invention, the present invention also provides a method for preparing continuous casting mold protection slag for medium carbon high chromium steel billet, comprising the following steps: Step 1: Preparation of modified fly ash: (1) Ultrafinely grinding fly ash to a particle size of 5-10 μm to obtain ultrafine fly ash powder; (2) Dissolve DL-tartaric acid in water to prepare a 1-3% DL-tartaric acid solution; stir the ultrafine fly ash powder at a low speed of 50-100 rmin, and spray the DL-tartaric acid solution on the ultrafine fly ash powder using a spraying device, and control the temperature below 35°C; after spraying, the DL-tartaric acid solution covers the surface of the ultrafine fly ash powder, and then quickly heats to 150-155°C and stirs for reaction for 3-5 hours; The concentration of DL-tartaric acid solution increases rapidly. Due to the fast heating speed, the DL-tartaric acid solution on the surface of the fly ash ultrafine powder boils locally, forming small bubbles, leaving some tiny pits or traces on the surface of the fly ash ultrafine powder. When the water is completely evaporated, DL-tartaric acid will form a solid film on the surface of the fly ash ultrafine powder. (3) Dissolve sodium polyphosphate in hot water at 90-92°C to prepare a 4-5% sodium polyphosphate solution, spray the sodium polyphosphate solution on the ultrafine fly ash powder using a spraying device, stir and react for 1-2 hours at a reaction temperature of 155-182°C to obtain modified fly ash; Step 2: Mix CaO 25.6-26.5%, SiO2 40-45%, Al2O3 6-11%, Na2CO3 8-10.3%, ZnO 5.4-8.5% and the remainder of modified fly ash to obtain mold protection slag.
[0015] In order to better achieve the purpose of the present invention, the present invention also provides an application of the mold protection slag in the continuous casting of medium-carbon high-chromium steel billets.
[0016] Compared with the prior art, the present invention has the following beneficial effects: the continuous casting crystallizer protection slag of the present invention has appropriate binary basicity, has good lubrication effect, and is conducive to reducing the generation of cracks; the continuous casting crystallizer protection slag of the present invention has appropriate melting point, which can improve the heat flow effect in the crystallizer; the continuous casting crystallizer protection slag of the present invention has appropriate viscosity, which can reduce the quality problems of medium carbon high chromium steel billets and improve the yield rate. At the same time, the present invention has abundant raw material sources, and utilizes the discarded shells and fly ash from the seafood processing industry and power plant, which not only reduces their adverse effects on the environment, but also broadens the raw material channels of the protection slag and improves the comprehensive utilization rate of resources. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Embodiment 1: In some embodiments, a method for preparing a continuous casting mold slag for a medium carbon high chromium steel billet comprises the following steps: Step 1: Preparation of modified fly ash: (1) Ultrafinely grinding fly ash to a particle size of 5 μm to obtain ultrafine fly ash powder; (2) Dissolve DL-tartaric acid in water to prepare a 1% DL-tartaric acid solution; stir the ultrafine fly ash powder at a low speed of 50 rmin, and spray the DL-tartaric acid solution on the ultrafine fly ash powder using a spraying device, and control the temperature below 35°C; after spraying, the DL-tartaric acid solution covers the surface of the ultrafine fly ash powder, and then quickly heats up to 150°C and stirs for 3 hours; The concentration of DL-tartaric acid solution increases rapidly. Due to the fast heating speed, the DL-tartaric acid solution on the surface of the fly ash ultrafine powder boils locally, forming small bubbles, leaving some tiny pits or traces on the surface of the fly ash ultrafine powder. When the water is completely evaporated, DL-tartaric acid will form a solid film on the surface of the fly ash ultrafine powder. (3) Dissolve sodium polyphosphate in 90°C hot water to prepare a 4% sodium polyphosphate solution, spray the sodium polyphosphate solution on the ultrafine fly ash powder using a spraying device, stir and react for 1 hour at a reaction temperature of 155°C to obtain modified fly ash; The mass ratio of the sodium polyphosphate to DL-tartaric acid is 1:0.3; the mass ratio of the sodium polyphosphate to fly ash is 3.2:100.
[0019] Step 2: Mix 25.6% of CaO, 45% of SiO2, 6% of Al2O3, 10.3% of Na2CO3, 5.4% of ZnO and the remainder of modified fly ash to obtain mold protection slag.
[0020] The CaO is derived from the shell calcination products discarded from the seafood processing industry and seafood restaurants; SiO2 comes from river sand, and the SiO2 content is above 80%; Al2O3 comes from diaspore, and the Al2O3 content is above 85%; Fly ash comes from fly ash in power plants.
[0021] Physical and chemical properties: binary basicity is 0.83, melting point is 925℃, viscosity is 0.62Pa•s at 1300℃.
[0022] Embodiment 2: In some embodiments, a method for preparing a continuous casting mold protection slag for a medium carbon high chromium steel billet comprises the following steps: Step 1: Preparation of modified fly ash: (1) Ultrafinely grinding fly ash to a particle size of 10 μm to obtain ultrafine fly ash powder; (2) Dissolve DL-tartaric acid in water to prepare a 3% DL-tartaric acid solution; stir the ultrafine fly ash powder at a low speed of 100 rmin, and spray the DL-tartaric acid solution on the ultrafine fly ash powder using a spraying device, and control the temperature below 35°C; after spraying, the DL-tartaric acid solution covers the surface of the ultrafine fly ash powder, and then quickly heats up to 155°C and stirs for reaction for 5 hours; The concentration of DL-tartaric acid solution increases rapidly. Due to the fast heating speed, the DL-tartaric acid solution on the surface of the fly ash ultrafine powder boils locally, forming small bubbles, leaving some tiny pits or traces on the surface of the fly ash ultrafine powder. When the water is completely evaporated, DL-tartaric acid will form a solid film on the surface of the fly ash ultrafine powder. (3) Dissolve sodium polyphosphate in 92°C hot water to prepare a 5% sodium polyphosphate solution, spray the sodium polyphosphate solution on the ultrafine fly ash powder using a spraying device, stir and react for 2 hours at a reaction temperature of 182°C to obtain modified fly ash; The mass ratio of the sodium polyphosphate to DL-tartaric acid is 1:0.6; the mass ratio of the sodium polyphosphate to fly ash is 6.5:100.
[0023] Step 2: Mix 26.5% of CaO, 40% of SiO2, 11% of Al2O3, 8% of Na2CO3, 8.5% of ZnO and the remainder of modified fly ash to obtain mold protection slag.
[0024] The CaO is derived from the shell calcination products discarded from the seafood processing industry and seafood restaurants; SiO2 comes from river sand, and the SiO2 content is above 80%; Al2O3 comes from diaspore, and the Al2O3 content is above 85%; Fly ash comes from fly ash in power plants.
[0025] Physical and chemical properties: binary basicity is 0.88, melting point is 942℃, viscosity is 0.75Pa•s at 1300℃.
[0026] Embodiment 3: In some embodiments, a method for preparing continuous casting mold protection slag for medium carbon high chromium steel billet comprises the following steps: Step 1: Preparation of modified fly ash: (1) Ultrafinely grinding fly ash to a particle size of 8 μm to obtain ultrafine fly ash powder; (2) Dissolve DL-tartaric acid in water to prepare a 2.5% DL-tartaric acid solution; stir the ultrafine fly ash powder at a low speed of 70 rmin, and spray the DL-tartaric acid solution on the ultrafine fly ash powder using a spraying device, and control the temperature below 35°C; after spraying, the DL-tartaric acid solution covers the surface of the ultrafine fly ash powder, and then quickly heats up to 153°C and stirs for 4 hours; The concentration of DL-tartaric acid solution increases rapidly. Due to the fast heating speed, the DL-tartaric acid solution on the surface of the fly ash ultrafine powder boils locally, forming small bubbles, leaving some tiny pits or traces on the surface of the fly ash ultrafine powder. When the water is completely evaporated, DL-tartaric acid will form a solid film on the surface of the fly ash ultrafine powder. (3) Dissolve sodium polyphosphate in 91°C hot water to prepare a 4.5% sodium polyphosphate solution, spray the sodium polyphosphate solution on the ultrafine fly ash powder using a spraying device, stir and react for 1.5 hours at a reaction temperature of 168°C to obtain modified fly ash; The mass ratio of the sodium polyphosphate to DL-tartaric acid is 1:0.5; the mass ratio of the sodium polyphosphate to fly ash is 4.2:100.
[0027] Step 2: Mix CaO 26.0%, SiO2 44%, Al2O3 8.5%, Na2CO3 9.5%, ZnO 7.0% and the remainder of modified fly ash to obtain mold protection slag.
[0028] The CaO is derived from the shell calcination products discarded from the seafood processing industry and seafood restaurants; SiO2 comes from river sand, and the SiO2 content is above 80%; Al2O3 comes from diaspore, and the Al2O3 content is above 85%; Fly ash comes from fly ash in power plants.
[0029] Physical and chemical properties: binary basicity is 0.91, melting point is 960℃, viscosity is 0.68Pa•s at 1300℃.
[0030] The continuous casting crystallizer protection slag of the present invention has a suitable binary basicity, has a good lubricating effect, and is conducive to reducing the generation of cracks; the continuous casting crystallizer protection slag of the present invention has a suitable melting point, which can improve the heat flow effect in the crystallizer; the continuous casting crystallizer protection slag of the present invention has a suitable viscosity, which can reduce the quality problems of medium-carbon high-chromium steel billets and improve the yield rate. At the same time, the raw material source of the present invention is rich, and the shells discarded by the seafood processing industry and the fly ash of the power plant are utilized, which not only reduces their adverse effects on the environment, but also broadens the raw material channels of the protection slag and improves the comprehensive utilization rate of resources.
[0031] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. Continuous casting mold protection slag for medium carbon high chromium steel billet, characterized in that: Its chemical composition and weight percentage are: CaO 25.6-26.5%, SiO2 40-45%, Al2O3 6-11%, Na2CO3 8-10.3%, ZnO 5.4-8.5% and the balance of modified fly ash; the modified fly ash is the product of fly ash modified by sodium polyphosphate and DL-tartaric acid.
2. The continuous casting mold protection slag for medium carbon high chromium steel billet according to claim 1, characterized in that: The mass ratio of the sodium polyphosphate to DL-tartaric acid is 1:0.3-0.
6.
3. The continuous casting mold protection slag for medium carbon high chromium steel billet according to claim 2, characterized in that: The mass ratio of the sodium polyphosphate to fly ash is 3.2-6.5:
100.
4. The continuous casting mold protection slag for medium carbon high chromium steel billet according to claim 3, characterized in that: The preparation method of the modified fly ash is: (1) Ultrafinely grinding fly ash to a particle size of 5-10 μm to obtain ultrafine fly ash powder; (2) Dissolve DL-tartaric acid in water to prepare a 1-3% DL-tartaric acid solution; stir the ultrafine fly ash powder at a low speed of 50-100 rmin, and spray the DL-tartaric acid solution on the ultrafine fly ash powder using a spraying device, and control the temperature below 35°C; after spraying, the DL-tartaric acid solution covers the surface of the ultrafine fly ash powder, and then quickly heats to 150-155°C and stirs for reaction for 3-5 hours; The concentration of DL-tartaric acid solution increases rapidly. Due to the fast heating speed, the DL-tartaric acid solution on the surface of the fly ash ultrafine powder boils locally, forming small bubbles, leaving some tiny pits or traces on the surface of the fly ash ultrafine powder. When the water is completely evaporated, DL-tartaric acid will form a solid film on the surface of the fly ash ultrafine powder. (3) Dissolve sodium polyphosphate in hot water at 90-92°C to prepare a 4-5% sodium polyphosphate solution, spray the sodium polyphosphate solution on the ultrafine fly ash powder using a spraying device, stir and react for 1-2 hours at a reaction temperature of 155-182°C to obtain modified fly ash.
5. The continuous casting mold protection slag for medium carbon high chromium steel billet according to claim 4, characterized in that: The CaO is derived from shell calcination products discarded from the seafood processing industry.
6. The continuous casting mold protection slag for medium carbon high chromium steel billet according to claim 5, characterized in that: SiO2 comes from river sand, and the SiO2 content is above 80%.
7. The continuous casting mold protection slag for medium carbon high chromium steel billet according to claim 6, characterized in that: Al2O3 comes from diaspore, and the Al2O3 content is above 85%.
8. The continuous casting mold protection slag for medium carbon high chromium steel billet according to claim 7, characterized in that: Fly ash comes from fly ash in power plants.
9. A method for preparing continuous casting mold powder for medium carbon high chromium steel billet according to claim 8, characterized in that: The following steps are involved: Step 1: Preparation of modified fly ash: (1) Ultrafinely grinding fly ash to a particle size of 5-10 μm to obtain ultrafine fly ash powder; (2) Dissolve DL-tartaric acid in water to prepare a 1-3% DL-tartaric acid solution; stir the ultrafine fly ash powder at a low speed of 50-100 rmin, and spray the DL-tartaric acid solution on the ultrafine fly ash powder using a spraying device, and control the temperature below 35°C; after spraying, the DL-tartaric acid solution covers the surface of the ultrafine fly ash powder, and then quickly heats to 150-155°C and stirs for reaction for 3-5 hours; The concentration of DL-tartaric acid solution increases rapidly. Due to the fast heating speed, the DL-tartaric acid solution on the surface of the fly ash ultrafine powder boils locally, forming small bubbles, leaving some tiny pits or traces on the surface of the fly ash ultrafine powder. When the water is completely evaporated, DL-tartaric acid will form a solid film on the surface of the fly ash ultrafine powder. (3) Dissolve sodium polyphosphate in hot water at 90-92°C to prepare a 4-5% sodium polyphosphate solution, spray the sodium polyphosphate solution on the ultrafine fly ash powder using a spraying device, stir and react for 1-2 hours at a reaction temperature of 155-182°C to obtain modified fly ash; Step 2: Mix CaO 25.6-26.5%, SiO2 40-45%, Al2O3 6-11%, Na2CO3 8-10.3%, ZnO 5.4-8.5% and the remainder of modified fly ash to obtain mold protection slag.
10. Use of the mold protection slag according to claim 9 in continuous casting of medium carbon high chromium steel billets.